ANALYSIS OF STUDENT ERRORS BASED ON NEWMAN’S THEORY IN SOLVING CONTEXTUAL PROBLEMS ON PROBABILITY - Zefanya Tabita Ambarita; Yokebet Hutapea; Romaida Fitriani Br Manik; Sri Vioni Novena Simanihuruk; Budi Halomoan Siregar (Pedagogy: Jurnal Pendidikan Matematika, 2026)
Mathematics instruction is essential for fostering logical thinking, organized reasoning, and the ability to tackle problems. Yet, in reality, numerous learners continue to face challenges when dealing with real-world problems, especially in the area of probability. The objective of this research is to examine the mistakes made by students when applying Newman’s Theory to solve real-world issues in probability. This study employs a qualitative approach using error analysis as the research method. Research subjects were selected using purposive sampling, specifically students who had studied probability. A total of 22 students participated in this study. Data gathering was carried out using written assessments featuring open-ended queries and interviews to understand the ways students think when tackling problems. The analysis of the data was performed utilizing the Newman method, which comprises reading mistakes, misunderstanding errors, transformation mistakes, procedural skill errors, and encoding mistakes. The findings from the research reveal that students made errors as follows: reading mistakes accounted for 4.54%, comprehension errors were at 10.6%, transformation mistakes reached 25.75%, process skill errors were at 36.36%, and encoding mistakes, which were the most common, were at 45.45%. These results show that learners continue to encounter major challenges when it comes to documenting step-by-step solution methods and delivering correct final responses that fit the situation of the problem. This study implies that mathematics instruction needs to emphasize conceptual understanding, mathematical modeling skills, and the practice of solving problems in a structured manner.